2021
DOI: 10.1177/15271544211050611
|View full text |Cite
|
Sign up to set email alerts
|

Policy Advocacy and Nursing Organizations: A Scoping Review

Abstract: Policy advocacy is a fundamental component of nursing's social mandate. While it has become a core function of nursing organizations across the globe, the discourse around advocacy has focused largely on the responsibilities and accountabilities of individual nurses, with little attention to the policy advocacy work undertaken by nursing organizations. To strengthen this critical function, an understanding of the extant literature is needed to identify areas that require further research. We conducted a scopin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 77 publications
2
20
0
Order By: Relevance
“…While some of the findings pertaining to priority setting and common advocacy strategies align with what is already known in the available body of literature (Chiu et al, 2021), the new knowledge generated from this study offers a unique perspective on policy advocacy undertaken by professional nursing associations in the context of a large‐scale public health crisis. Specifically, this new knowledge includes insights about the role and target audience of nursing associations, the breadth and depth nursing associations' policy advocacy agendas during a pandemic, how leaders working in nursing associations negotiate internal and external factors to determine their policy priorities and advocacy strategies, and their perspectives on policy advocacy evaluation.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…While some of the findings pertaining to priority setting and common advocacy strategies align with what is already known in the available body of literature (Chiu et al, 2021), the new knowledge generated from this study offers a unique perspective on policy advocacy undertaken by professional nursing associations in the context of a large‐scale public health crisis. Specifically, this new knowledge includes insights about the role and target audience of nursing associations, the breadth and depth nursing associations' policy advocacy agendas during a pandemic, how leaders working in nursing associations negotiate internal and external factors to determine their policy priorities and advocacy strategies, and their perspectives on policy advocacy evaluation.…”
Section: Discussionsupporting
confidence: 74%
“…The extant literature offers a snapshot of the breadth and depth of policy issues that nursing organizations have advocated (Chiu et al, 2021); however, the findings in this study offer a unique lens into the kinds of issues that are relevant to professional nursing associations during a global pandemic. In the context of Shamian's (2014) Spheres of Influence Model, organizations included in the study demonstrated their careful attention to policy issues in the nursing, health and public policy spheres at the regional, national, and global levels.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Literature contribution comes from other seemingly unrelated yet equally valuable sources, such as from reviews of established international organizations (Barrett et al, 2016; IOB Evaluation, 2015; Oxfam, 2014), from generalized academic frameworks (Chapman & Wameyo, 2001; Moore et al, 2013) and from related fields within public health research (Cullerton et al, 2018; Harris-Roxas & Harris, 2011; Kemm, 2001; Veerman, Barendregt, et al, 2006; Veerman, Bekker, et al, 2006). Some studies have delved in analysing purely the ‘advocacy’ dimension of public health (Chapman, 2001, 2004; David et al, 2020), while few studies reviewed also the role of nurses organizations in the process of policy influence and advocacy (Arabi & Ra, 2014; Catallo et al, 2014; Chiu et al, 2021; Moore et al, 2013; Spenceley et al, 2006; van Wijk et al, 2022).…”
Section: Towards a Consensus To Evaluate Policy Influence In Public H...mentioning
confidence: 99%
“…In North America there is a growing literature on nurse leaders’ influence on policy participation ( Waddell et al, 2017 ), governance ( Porter-O’Grady, 2017 ; Sundean et al, 2020 ), educating nurses in health policy ( Ellenbecker et al, 2017 ; Lewinski & Simmons, 2018 ; Sundean et al, 2019 ; Thomas et al, 2020 ), nursing service on boards of directors ( Prybil et al, 2019 ; Sundean et al, 2017 ), participation in professional nursing organizations ( Gebbie et al, 2000 ) and policy advocacy work ( Chiu et al, 2021 ). In line with other literature, we defined nurse leaders broadly in order to include both formal and informal roles and positions, in and outside the healthcare organization (see for example Cummings et al, 2018 or Sundean et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%